Análise da influência do compartilhamento da informação e da complexidade da tarefa na decisão em grupo - Visentini, Monize Sâmara (2010)
Decision making is crucial for enterprises, being frequently done by groups. However, the way information is shared among groups, as well as the complexity of the task being analyzed might affect the quality of group decision. Thus, the following research aims to identify how information sharing and task complexity influence on group decision. Besides, it is aimed to (a) validate a decisive task related to information sharing and task complexity; b) verify the way information sharing affects taking decisions in groups and; c) illustrate the effect of task complexity in group decisive process. Four hypotheses were drawn in order to corroborate these objectives. The methodology applied was an almost-experimental research conducted in a laboratory, having as independent variables the information sharing and task complexity; and as a dependent variable, group decision. In order to contemplate those variables, the applied task has been adapted from Stasser and Stewart (1992) and Fraidin (2004), and is denominated Murder Mystery . This task went through a process of reverse translation, cultural adaptation, and two validations corroborating the first specific objective of this research. It was used a system for data collection developed specifically for the experiment, STAR Individual x SER Grupo . Besides, group discussions were followed by observers previously trained and recorded for further analysis. Qualitative and quantitative analyses were conducted. The number of undergraduate students taking part in the experiment was 144. Concerning specific objectives, it was observed that there were no differences between the quality of the decision from both groups, independently of the type of information sharing, good decisions were taken. Fisher s test has been applied to the decisions with total and partial sharing. It was also compared the decisions taken by groups that mad a simple task and the ones of a complex one, with no statistically significance for Fisher s test, leading to the fact that there is no difference between the quality of the decision taken by groups that made a simple task and groups that made complex ones. However, the more a task is complex; the less information is discussed by a member of the group, jeopardizing decision making. All the research objectives were reached. In a general sense, through testing four hypotheses, there was no influence of information sharing and task complexity in group decision, opposing a great part of the literature, indicating that more studies on this topic are necessary.